Association of gastro esophageal reflex with chronic asthma and its significance: a prospective study - Daruru, Rangnath; Mahadevan, Shanker; Kokiwar, Prashant R. (International Journal of Contemporary Pediatrics, 2017)
Background: Many studies have reported that gastro esophageal reflux is significantly more common in asthmatics than in control populations and this appears to apply particularly in childhood. To study the incidence of gastro esophageal refluxes in children which chronic asthma. To identity the clinical characteristic in children with chronic asthma and GER, which would predict reflux, related asthma? Methods: It is a prospective study of association of GER and chronic asthma using Radio nuclide scintigraphy carried at General pediatric in-patient wards of Niloufer hospital, Hyderabad. A Total of 50 patients with chronic asthma and 15 healthy children were evaluated. Results: Our study showed an incidence of Gastro Esophageal Reflux (GER) in 42% of chronic asthmatic children. High incidence of reflux (47.6%) under 4 years of age. No significance difference in the incidence of GER in children with seasonal verus Non-Seasonal asthma. About 50% of children with GER had no symptoms i.e. they had silent reflux. Nocturnal symptoms were significantly higher in asthmatic children with Ger (54.8%) than asthmatic children without GER (21%). Children with reflux related asthma suffered more morbidity in terms of recurrence of attacks, severity of chronic asthma (moderate persistent) and sleep disturbance as compared to children with no reflux. Presence of atopic signs was significantly higher in patients with asthma without GER. Conclusions: GER should be considered as a potentially important contributing factor in any patient with poorly controlled asthma. The asthmatic patient most likely to experience measurable benefit from anti-reflux therapy is the patients with significant nocturnal asthma and who have symptoms of both asthma and of reflux.